PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS CONTEXTUAL TEACHING AND LEARNING PADA MATERI ARITMETIKA SOSIAL - Sudirmawati Buulolo (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2022)
The purpose of this study is to develop a Student Worksheet based on Contextual Teaching and Learning on valid, practical, and effective social arithmetic material. The type of research used in this research is research and development or (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques used are validation sheets, student response questionnaires, and student learning outcomes tests. While the data analysis technique used is qualitative and quantitative data analysis. Based on research and discussion that the results of the material expert's validation were 94.4% with very decent criteria, the validation results from media experts were 82.2% with very feasible criteria, and the validation results from linguists were 98% with very feasible criteria. The results of the practicality test of the individual trial respondents were 70.33% with interesting and practical criteria, the results of the small group trial respondents were 81% with a very interesting and very practical category, and the results of the field trial respondents were 81% with a very interesting and very attractive category. very practical. The results of the effectiveness obtained an average value of 84.5% with a very high category. The researcher hopes that this worksheet can make it easier for students to understand the concept of social arithmetic material.